Pertukaran Sosial Antara Pimpinan Dengan Karyawan Di Toko Kusuma Jaya Denpasar - Rukningsih, Ni Putu Sri Veni; Nugroho, Wahyu Budi; Mahadewi, Ni Made Anggita Sastri (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 3 No 2 (2023): JISSOROT, 2023)
This study aims to analyze social exchanges between leaders and employees at Kusuma Jaya Shop Denpasar, one of the retail stores in the North Denpasar region. This research uses a qualitative approach with descriptive and explanatory types. The author uses three propositions from George Caspar Homans' six propositions of social exchange theory, namely the success proposition, the stimulus proposition and the value proposition. The dynamics of work at Toko Kusuma Jaya such as the number of employees, division of labor and the development of turnover have an influence on social exchange. Social exchange at Kusuma Jaya Shop occurs statically, in the process the propositions in Homans' social exchange theory are attributed in this study as the basis of individual behavior in making exchanges. The proposition is done by the individual to minimize the losses gained .